ANALISIS WACANA HIDUP MATI LISTRIK PADA PROGRAM TALK SHOW MATA NAJWA DI STASIUN TV TRANS 7 - Pratama, Yogi; Abidin, Sholihul (LPPM Universitas Putera Batam, 2020)
Critical Discourse Analysis is always interesting to study more deeply. The power of the media and public perception that makes critical discourse research continue to grow. The formulation of the problem in this research is how is the analysis of the critical discourse of Van Djik's model in the Mata Najwa program episode